PENGOLAHAN LIMBAH IKAN PATIN MENJADI BIODIESEL - Harahap, Muharram Fajrin; Bahri, Saiful (Jurnal Kajian Lingkungan, 2013)
Research executed from May to July 2011 in the village of LubukAgung Koto Masjid XIIIKoto Kampar and Laboratory Testing and Analysis Chemistry Faculty of Engineering,University of Riau. The purpose of this research was to reduce the problem of the odorgenerated from patin fish waste and determine the characteristic properties of biodiesel andcompared with the characteristic properties of biodiesel standards.From the result ofresearch showed that the utilization of waste belly patin fish is one effort that supports theactivities of Zero Waste. Besides with a view to reducing the impact of odor pollution andinconvenience, it also produced another positive impact of its products, namely biodiesel isenvironmentally friendly energy.Based on tests conducted level of smell, it is known thatsewage smell catfish rated by respondents with a percentage of 56.3%. Following the laterrather smell a percentage of 31.3% and expressed more smell as much as 12.5%.The processof making biodiesel with a variation of mol% of catalyst and the comparison of resultsobtained at a maximum of 85.447 grams of 1.5% treatment% catalyst and mole ratio of 3:1and the optimal treatment for 79.173 grams of the catalyst 0.5% and the mole ratio of 3:1.Comparison of quality characteristics of biodiesel showed values in accordance with ISObiodiesel.